Dampak Green Hotel Standards Terhadap Preferensi Menginap Wisatawan (Studi Kasus Pulau Macan Eco Lodge) - Ronauli Arindra; Irena Novarlia (Publikasi Indonesia, 2025)
This study aims to examine the impact of implementing green hotel standards on tourist lodging preferences at Pulau Macan Eco Lodge, located in the Thousand Islands. The research applies a quantitative approach using a case study method. Primary data were collected through questionnaires distributed to previous guests and interviews with hotel management. Secondary data were gathered through documentation and literature review. The research instrument covers eco-friendly product use, waste management, energy efficiency, and consumer attitudes and intentions toward green hotels. Data analysis includes validity and reliability tests, descriptive statistics, case study analysis, and simple linear regression using SPSS. The results indicate that the implementation of green hotel standards significantly influences tourists’ preferences to choose, revisit, and recommend Pulau Macan Eco Lodge. These findings highlight the importance of sustainable practices in the hospitality industry as a determinant of consumer behavior.